Conflict and Compromise, Discourse and Action: Political Ecology in the Complexity of Land Management in Central Kalimantan, Indonesia - Meilinda, Salsa Rizkia; Salman, Darmawan; Muhammad, Sawedi (Forest and Society, 2025)
Peatlands in Mantangai District, Central Kalimantan, have emerged as a site of contention among many stakeholders with differing interests, illustrating the intricacies of natural resource management in Indonesia. This research seeks to examine the contestation process, identify main actors, and comprehend how various forms of knowledge and power influence the results of peatland management. This research employs a case study method with a qualitative approach, incorporating direct observation, in-depth interviews, and document analysis to achieve a thorough knowledge of the dynamics of contestation. The findings indicate three primary viewpoints in peatland management: eco-conservationism exemplified by Mawas Borneo Orangutan Survival Foundation (BOSF), eco-developmentalism illustrated by the government's food estate initiative and oil palm plantation expansion, and eco-populism promoted by Wahana Lingkungan Hidup (WALHI) Central Kalimantan and local communities. This contention leads to multiple underlying conflicts, including tensions between conservation initiatives and resource extraction activities by local communities, discrepancies between governmental development programs and the ecological and social realities, as well as unresolved land disputes and compensation challenges arising from the expansion of oil palm plantations. This study suggests that a more holistic and inclusive approach to peatland management is necessary, taking into account ecological, economic, and socio-cultural factors in a balanced manner. These findings significantly enhance the comprehension of the intricacies of natural resource management and can underpin the formulation of more inclusive and sustainable policies moving forward.